(Re)constructing Ageing Futures: Insights from Migration in Asia and Beyond. (December 2022) - Ho, Elaine Lynn-Ee; Thang, Leng Leng; Huang, Shirlena; Yeoh, Brenda S.A.
This special issue examines how older adults anticipate and manage their futures through migration. Although ageing is often associated with decline towards the end-of-life, it is still a life stage where (the lack of) planning for the future can profoundly impact the life outcomes of older adults and their caregivers. This collection illustrates different ways migration can impact ageing. For some, perceptions and depictions of the future lead older adults to turn to migration to improve their prospects of ageing well although they continue to face constraints while ageing abroad. For others, the migration of younger family members exacerbates the stress of eldercare felt by non-migrant caregivers. Collectively, the papers focus on how countries in Asia function as source and destination sites for ageing-related migration, while also forging transnational connections with the Global North. Focusing on ageing futures allows us to link the current and future lives of migrants and non-migrants, across generations and space.